2005
DOI: 10.1002/ajpa.20084
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of cusp dimensions in human maxillary molars

Abstract: Cusp dimensions of human maxillary molars were compared between males and females to determine whether the later-developed, distal cusps displayed greater sexual dimorphism than the earlier-developed, mesial cusps, and whether the later-forming second molar displayed greater sexual dimorphism than the first molar. First and second permanent molar crowns (M1 and M2) were measured indirectly, using dental casts obtained from 117 Japanese (65 males and 52 females). Measurements included maximum mesiodistal and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
80
1
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 29 publications
13
80
1
8
Order By: Relevance
“…In addition, both men and women had greater measurements with respect to the total cusp area, area of occlusal table, and occlusal table ratio in the first molars than in the second molars. These results correspond with the results of previous studies, which showed that the faster the cusp develops, the greater the cusp becomes, i.e., late-developing teeth more frequently have reduced overall size than early-developing teeth because the former have more spatial restrictions [3,5,8,10,[18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, both men and women had greater measurements with respect to the total cusp area, area of occlusal table, and occlusal table ratio in the first molars than in the second molars. These results correspond with the results of previous studies, which showed that the faster the cusp develops, the greater the cusp becomes, i.e., late-developing teeth more frequently have reduced overall size than early-developing teeth because the former have more spatial restrictions [3,5,8,10,[18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 91%
“…There may be two explanations for no significant sex difference in the size of the hypoconulid of the mandibular second molars. First, the latest-calcifying hypoconulid has the greatest variability and the hypoconulid appears less frequently in mandibular second molars because of greater spatial restrictions than mandibular first molars [8,10]. Secondly, it might be assumed that the periods of completion of mandibular first and second molar cusp formation (mandibular first molar: 2.5~3 years of age, mandibular second molar: 7~8 years of age) are much before adolescence, during which there is production and secretion of sex hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of sexual dimorphism in the size of the temporary and permanent teeth is a fact welldocumented in humans and primates (Garn et al, 1967;Garn et al, 1977;Scott & Turner, 1997;Kondo et al, 1998;Kondo et al, 2005;TeschlerNicola, 1992;Wood et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies indicate that the mandibule canine is the tooth that presents greater dimorphism, followed by the first and second maxillary molars (Acharya & Mainali, 2007;Kondo et al, 1998;Kondo et al, 2005;Ling & Wong, 2006). In our work, the significant differences were found mainly in bucolingual diameters, but theyincluded various teeth of all dental groups, the largest being found in teeth 4.4 and 4.7, these results are similar to those reported by Ruiz in a Chilean population similar to this study, which reinforces the arguments (Alt et al, 1998) that changes in dental dimensions are influenced by ethnic factors.…”
Section: Discussionmentioning
confidence: 99%